T Cell Vaccination Inhibits Th1/Th17/Tfh Frequencies and Production of Autoantibodies in Collagen-Induced Arthritis - Shan Li; Xiaoyin Niu; Yebin Xi; Shaohua Deng; Chengzhen Li; Qing Zhao; Guangjie Chen (Clinical and Developmental Immunology, 2013)
The aim of this study is to determine whether the regulatory role of T cell vaccination (TCV) is through inhibition of Th1/Th17/Tfh and production of autoantibodies on collagen-induced arthritis (CIA). First, CIA mice were treated with TCV. After disease onset, the incidence and severity of change in joint histopathology were evaluated. Mice in the TCV-treated group showed less disease severity and less infiltration of inflammatory cells in the joint sections. TCV decreased the frequencies of Th1/Th17/Tfh cells and related cytokines. Reduction of IL-21 may be associated with both Tfh and Th17, which further influence B cell and T cell responses. In addition, inhibition of Th1/Th17/Tfh frequencies led to the reduced expression of T-bet, RORα, RORγt, and Bcl6. Lastly, the proliferation of type-II-collagen-(CII-) specific T cells and the production of anti-CII antibodies were inhibited in the TCV-treated group. The results provide novel evidence that the therapeutic effects of TCV on CIA are associated with the inhibition of Th1/Th17/Tfh frequencies and autoantibodies production.